Modeling, Analysis and Optimization for Mathematical Finance, Economics and Risks (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
Modeling, Analysis, and Optimization for Mathematical Finance, Economics, and Risks is a critical domain that integrates mathematical theory with practical applications to address the complexities of modern financial and economic systems. This special issue focuses on recent studies that are helping to develop sophisticated mathematical models to better understand, predict, and optimize financial markets, economic behaviors, and risk management. These studies, as well as the theoretical results and practical applications contained in this reprint, underscore the importance of a rigorous, quantitative approach to navigate and master the intricacies of these interconnected fields. This synergy not only advances theoretical understanding but also drives practical innovations, ensuring robustness and resilience in a rapidly evolving global landscape of modern quantitative techniques for financial mathematics, actuarial science and operational research.